2013
DOI: 10.1101/gad.212308.112
|View full text |Cite
|
Sign up to set email alerts
|

PQBP1, a factor linked to intellectual disability, affects alternative splicing associated with neurite outgrowth

Abstract: Polyglutamine-binding protein 1 (PQBP1) is a highly conserved protein associated with neurodegenerative disorders. Here, we identify PQBP1 as an alternative messenger RNA (mRNA) splicing (AS) effector capable of influencing splicing of multiple mRNA targets. PQBP1 is associated with many splicing factors, including the key U2 small nuclear ribonucleoprotein (snRNP) component SF3B1 (subunit 1 of the splicing factor 3B [SF3B] protein complex). Loss of functional PQBP1 reduced SF3B1 substrate mRNA association and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 49 publications
4
60
0
Order By: Relevance
“…In their study, knockdown of PQBP1 profoundly impaired the formation of the primary cilium in hippocampal neurons and the mouse cerebral cortex in vivo 31 . These results suggest that the loss of function of PQBP1 is responsible for the biological dysfunctions underlying mental retardation disorders 12,[19][20][21][22] .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In their study, knockdown of PQBP1 profoundly impaired the formation of the primary cilium in hippocampal neurons and the mouse cerebral cortex in vivo 31 . These results suggest that the loss of function of PQBP1 is responsible for the biological dysfunctions underlying mental retardation disorders 12,[19][20][21][22] .…”
Section: Discussionmentioning
confidence: 89%
“…PQBP1 is dominantly expressed in the central nervous system in embryos and in newborn mice 20 , and PQBP1 knockdown results in impairment of anxiety-related cognition and memory 19 . A recent study by Wang et al 22 has shown that PQBP1 knockdown in primary mouse neurons results in aberrant alternative splicing of pre-mRNAs that are important for neuron projection development, although the precise mechanism by which this occurs remains to be explored. In addition, Ikeuchi et al 31 have identified a function for PQBP1 in the morphogenesis of the primary cilium in postmitotic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…3A). To detect, compare, and quantitate differences in pre-mRNA splicing patterns between the full-length PSI and the PSIΔAB mutant, we used three different computational methods [MISO (12), JuncBase (13), and the Junction Use Model (JUM) (14)] (Fig. 3B, Fig.…”
Section: Psi Is Broadly Expressed In Both Male and Female Drosophila mentioning
confidence: 99%
“…Most human disease-causing PQBP1 mutations truncate the C-terminal domain of PQBP1 that is required for interaction with the spliceosomal protein U5-15kD (Waragai et al, 2000;Zhang et al, 2000). Knockdown of PQBP1 in mouse embryo primary neurons reduces general splicing efficiency and promotes the use of alternative splice sites in a variety of transcripts (Wang et al, 2013). A missense mutation within the WW domain at the N-terminus of PQBP1 in Golabi-Ito-Hall (GIH) patients (Y65C) causes abnormal pre-mRNA splicing and inhibits PQBP1 binding to spliceosome components and a partner protein, WBP11 (Lubs et al, 2006;Tapia et al, 2010;Sudol et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…PQBP1 interacts with the C-terminus of activated RNA polymerase II (Okazawa et al, 2002) and with spliceosome components, including U5-15kD (Dim1p) (Waragai et al, 2000;Zhang et al, 2000) and the U2 snRNP component Sf3b1 (Wang et al, 2013). Most human disease-causing PQBP1 mutations truncate the C-terminal domain of PQBP1 that is required for interaction with the spliceosomal protein U5-15kD (Waragai et al, 2000;Zhang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%